A Scoping Review Comparing Oral Microbial Diversity of Fixed Versus Removable Orthodontic Appliances in Mouth-Breathing Children - Marta Ulina Naibaho; Risti Saptarini Primarti (Journal of Social Research, 2026)
Mouth-breathing is a common condition among children undergoing orthodontic treatment, playing a significant role in altering the oral environment. Breathing through the mouth leads to changes in the humidity and temperature of the oral cavity, which can disrupt the balance of the oral microbiome. The study aims to systematically investigate oral microbial diversity in mouth-breathing children undergoing orthodontic treatment and assess the impact of each appliance type. The search process in this review was guided by predetermined clinical questions using the PCC framework: population (P), concept (C), and context (C). Relevant papers published between 2014 and 2024 were identified through PubMed, Scopus, and EBSCOhost databases, following PRISMA-ScR guidelines. Data extraction followed a structured approach, and the JBI Critical Appraisal Checklist was used to assess study quality. Of 204 papers identified, 6 studies met the inclusion criteria. Both appliance types led to shifts in microbial balance, with mouth-breathing children showing overgrowth of facultative anaerobes and reduced aerobic species. This influence appeared more pronounced with fixed appliances. Mouth-breathing in children undergoing orthodontic treatment significantly disrupts the oral microbiome, with fixed appliances showing a more pronounced negative impact on microbial diversity than removable appliances. Further longitudinal studies are required to explore the effects of oral hygiene interventions on the microbial environment and to inform clinical decision-making for better mouth-breathing management.